Effectiveness of Probiotim and Mecobalamin Supplementation as an Adjuvant Therapy for Acute Stroke: A Quasi-Experimental Study - ST Nur Indah Sari HS; Nurhikmah; Anita Amir (The International Journal of Medical Science and Health Research, 2026)
Introduction: Acute stroke is a leading cause of mortality and long-term disability worldwide. Beyond standard reperfusion and pharmacological therapies, adjuvant strategies targeting neuroinflammation and neural regeneration are crucial. This study aimed to evaluate the effectiveness of combining Probiotim (a probiotic immunomodulator) and Mecobalamin (an active form of vitamin B12) compared to Mecobalamin alone as an adjuvant therapy for acute stroke patients. Methods: A quasi-experimental study with a pre-test and post-test control group design was conducted at the Stroke Unit of Latemmamala Hospital, Soppeng, from October to December 2025. Ten acute ischemic stroke patients (<72 hours onset) were recruited using consecutive sampling and divided into two groups (n=5 each): an intervention group (Probiotim + Mecobalamin + standard therapy) and a control group (Mecobalamin + standard therapy). Neurological improvement and functional outcomes were assessed using the National Institutes of Health Stroke Scale (NIHSS) and Barthel Index at baseline and after 7-14 days of intervention. Data were analyzed using descriptive statistics and the Mann-Whitney U test due to non-normal distribution. Results: Both groups showed clinical improvement. In the intervention group, 40% of patients achieved mild dependence (Barthel Index) and 30% had moderate stroke (NIHSS-out), while in the control group, 30% achieved mild dependence and 20% had mild stroke (NIHSS-out). However, the Mann-Whitney U test revealed no statistically significant differences between the two groups for the Barthel Index (p = 0.439), NIHSS admission scores (p = 0.811), or NIHSS discharge scores (p = 0.729). No adverse events were reported in either group. Discussion: The lack of significant difference suggests that adding Probiotim to Mecobalamin did not provide superior short-term neurological recovery compared to Mecobalamin alone. This may be attributed to the small sample size (n=10), short intervention duration insufficient for probiotic gut colonization, the dominant and rapid neuroregenerative effect of Mecobalamin received by both groups, and the relatively mild baseline stroke severity. While Mecobalamin's neuroprotective role is supported by theory, the synergistic effect of probiotics through the gut-brain axis was not captured within the study's limitations. Conclusion: Both Probiotim+Mecobalamin and Mecobalamin alone are safe and associated with neurological improvement in acute stroke patients. However, the combination did not demonstrate statistically significant additional benefits over Mecobalamin alone for short-term outcomes. Larger, longer-term studies with a placebo-only control group and microbiome analysis are needed.